Self-fixable barrier membrane with gradient pores as well as preparation method and application of self-fixable barrier membrane
The self-fixing barrier membrane with gradient pore structure and double cross-linked network solves the mechanical strength and adhesion problems of Bio-Gide membrane, realizes the combination of barrier function and cell promotion, effectively regulates the osteogenic environment in bone defect areas, simplifies the preparation process and reduces costs.
Patent Information
- Application Number
- CN202511389317.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-26
- Publication Date
- 2025-12-19
AI Technical Summary
Existing Bio-Gide barrier membranes lack mechanical strength, making them difficult to resist forces inside and outside the oral cavity. They also lack adhesiveness, increasing the difficulty of surgery. Animal-derived membranes can lead to immunogenicity and cannot actively regulate the osteogenic microenvironment.
A self-fixing barrier membrane with gradient pores was prepared, comprising a barrier layer, a drug-loaded pore-forming layer, and an adhesion layer. The gradient structure is formed by the difference in pore size. The porous structure is formed by using methacrylamide gelatin and calcium ion crosslinked sodium alginate microspheres. Combined with the double crosslinked network of GelMA-DOP and polyacrylic acid, the membrane achieves both barrier function and cell-promoting function.
While ensuring mechanical strength, it achieves self-fixation of the barrier membrane and bone tissue, promotes osteoblast ingrowth, releases drugs through the degradation of calcium ion cross-linked microspheres, regulates the inflammation and osteogenic microenvironment in the bone defect area, simplifies the preparation process and reduces costs.
Smart Images

Figure CN121154949A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of tissue engineering and biomaterials, and particularly relates to a self-fixable barrier membrane with gradient porosity and a preparation method and application thereof. BACKGROUND
[0002] Guided bone regeneration (GBR) uses a membrane as a barrier to block the contact between gingival epithelium and connective tissue and root surface, so as to regenerate periodontal support tissue. The barrier membrane plays an important role as a key material in this technology. The commonly used Bio-Gide barrier membrane in the clinic is an absorbable collagen membrane processed from pig collagen, which has many limitations. First, its mechanical strength is poor and it is difficult to resist the external force borne by the oral cavity when it performs normal physiological functions. At the same time, it has no adhesion and is curled when it meets blood, which increases the difficulty of surgical operation and makes it difficult to achieve bone powder sealing. In addition, its animal origin has certain immunogenicity, and it cannot actively regulate the osteogenic microenvironment due to the lack of active substances. Therefore, an ideal biomaterial barrier membrane is urgently needed to meet various complex and contradictory needs, such as the balance of rigidity and flexibility, the matching of multiple liquid environments and adhesion function, the combination of dense barrier and porous structure, the sequential regulation of anti-inflammatory and osteogenic microenvironment.
[0003] Tissue engineering technology provides a new idea to solve the above problems. Among them, methacrylated gelatin has become a widely used biomaterial due to its excellent biocompatibility, mechanical properties and easy modification. However, its biological function is single, it has no wet adhesion, and it cannot simultaneously play the roles of barrier performance and cell ingrowth promotion, which limits its application in the field of barrier membranes. Therefore, the present application proposes a self-fixable barrier membrane with gradient porosity and a preparation method and application thereof. SUMMARY
[0004] The purpose of the present application is to provide a self-fixable barrier membrane with gradient porosity and a preparation method and application thereof, which aims to solve the problems raised in the background art.
[0005] The purpose of the present application is achieved by the following technical solutions:
[0006] A preparation method of a self-fixable barrier membrane with gradient porosity, the self-fixable barrier membrane comprising a barrier layer, a drug-loaded pore-forming layer and an adhesion layer from soft tissue to bone tissue surface in turn, and a gradient porosity structure is formed between the three layers through the difference in pore size; the preparation method comprises the following steps:
[0007] Preparation of the barrier layer: Gelatin with a strength of 250g Bloom was dissolved in ddH2O. After stirring and dissolving, methacrylic anhydride was added dropwise at a rate of 0.25ml / min and reacted at room temperature in the dark for 2h. After the reaction was completed, the solution was placed in a dialysis bag and dialyzed in the dark for 72h. After freeze-drying, GelMA lyophilized sponge was obtained. The GelMA lyophilized sponge was dissolved in ddH2O to obtain GelMA solution. The photoinitiator lithium phenyl (2,4,6-trimethylbenzoyl) phosphate was added, and a barrier layer was formed under ultraviolet light irradiation at a wavelength of 365nm.
[0008] Preparation of drug-loaded pore-forming layer: Sodium alginate was dissolved in ddH2O, stirred until dissolved, and sodium periodate was added. The reaction was carried out overnight at 4℃. After the reaction was completed, 500 μL of ethylene glycol was added to quench the reaction. The solution was placed in a dialysis bag and dialyzed in the dark for 72 h. After freeze-drying, OSA lyophilized sponge was obtained. OSA lyophilized sponge was dissolved in ddH2O to obtain OSA aqueous solution. 5-aminosalicylic acid aqueous solution prepared by dissolving 5-aminosalicylic acid in ddH2O was added. The reaction was carried out at room temperature for 72 h to obtain OSA composite 5-ASA solution. The solution was dripped into calcium chloride solution through a microfluidic chip to obtain uniformly sized calcium ion crosslinked OSA composite 5-ASA microspheres. The calcium ion crosslinked OSA composite 5-ASA microspheres were incorporated into GelMA solution, and phenyl (2,4,6-trimethylbenzoyl) lithium phosphate was added. The drug-loaded pore-forming layer was formed under ultraviolet light irradiation at a wavelength of 365 nm.
[0009] Preparation of the adhesive layer: GelMA lyophilized sponge was dissolved in ddH2O, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide were added to activate the amino groups on the GelMA molecular chain. Then, 3,4-dihydroxyphenylacetic acid was added, and the reaction was carried out overnight at 37°C in the dark. After the reaction was completed, the solution was placed in a dialysis bag and dialyzed in the dark for 72 hours. After freeze-drying, GelMA-DOP lyophilized sponge was obtained. GelMA-DOP lyophilized sponge was dissolved in ddH2O to obtain GelMA-DOP solution. Polyacrylic acid solution was added, and after stirring evenly, lithium phenyl (2,4,6-trimethylbenzoyl) phosphate was added. Under ultraviolet light irradiation at a wavelength of 365 nm, an adhesive double cross-linked network hydrogel ink was formed. The ink was printed on the side of the drug-loaded pore-forming layer away from the barrier layer using a 3D printer to form an adhesive layer with millimeter-scale 3D printed pores.
[0010] Furthermore, in preparing the barrier layer, the ratio of gelatin to methacrylic anhydride is 1000:0-1000 (g / mL); the ratio of GelMA lyophilized sponge to ddH2O is 0-20:100 (g / mL). Preferably, the ratio of gelatin to methacrylic anhydride is 1000:800 (g / mL); the ratio of GelMA lyophilized sponge to ddH2O is 1:10 (g / mL).
[0011] Furthermore, in preparing the drug-loaded pore-forming layer, the ratio of sodium alginate to ddH2O is 1-1000:100 (g / mL); the mass ratio of OSA lyophilized sponge to 5-aminosalicylic acid is 1-40:1; the ratio of calcium chloride to ddH2O in the calcium chloride solution is 1-50:100 (g / mL); and the pore size of the calcium ion-crosslinked OSA composite 5-ASA microspheres is 100-300 μm. Preferably, the ratio of sodium alginate to ddH2O is 1:100 (g / mL); the mass ratio of OSA lyophilized sponge to 5-aminosalicylic acid is 1:1; the ratio of calcium chloride to ddH2O in the calcium chloride solution is 5:100 (g / mL); and the pore size of the calcium ion-crosslinked OSA composite 5-ASA microspheres is 188 μm.
[0012] Furthermore, in preparing the adhesive layer, the mass ratio of GelMA lyophilized sponge to 3,4-dihydroxyphenylacetic acid is 1:0-10; the ratio of GelMA-DOP lyophilized sponge to ddH2O is 1-50:100 (g / mL); the volume ratio of GelMA-DOP solution to polyacrylic acid solution is 1:0-10; and the 3D printing pore size is 1-4 cm. Preferably, the mass ratio of GelMA lyophilized sponge to 3,4-dihydroxyphenylacetic acid is 1:1; the ratio of GelMA-DOP lyophilized sponge to ddH2O is 20:80 (g / mL); the volume ratio of GelMA-DOP solution to polyacrylic acid solution is 1:2; and the 3D printing pore size is 2 cm.
[0013] A self-fixing barrier membrane with gradient pores prepared according to the preparation method described above.
[0014] The application of the self-fixing barrier membrane described above in the preparation of a barrier material for guided bone regeneration.
[0015] Application of the self-fixing barrier membrane described above in the preparation of biomaterials for bone tissue repair.
[0016] Compared with the prior art, the beneficial effects of the present invention are:
[0017] The self-fixing barrier membrane prepared in this invention comprises a barrier layer, a drug-loaded pore-forming layer, and an adhesion layer sequentially from soft tissue to bone tissue, possessing gradient porosity and microenvironment sequential regulation functions. Functionally, on the one hand, its asymmetric structure promotes osteoblast ingrowth through its porous surface. The gradient porosity structure and adhesive double cross-linked network (formed by GelMA-DOP and PAA) provide greater strain resistance while ensuring mechanical strength. Furthermore, the abundant hydrogen bonds in the double cross-linked network allow it to adhere to bone tissue in a humid environment, achieving self-fixation to maintain positional stability in the surgical area, successfully combining barrier function and cell ingrowth promotion function. On the other hand, the calcium ion-crosslinked OSA composite 5-ASA microspheres, due to their different degradation rates from the GelMA matrix, can act as a pore-forming agent to form micron-sized pores in the drug-loaded pore-forming layer. During microsphere degradation, 5-ASA is rapidly released to exert an anti-inflammatory effect, and the released calcium... 2+ The protein is captured by the negatively charged PAA in the adhesion layer, enabling continuous release to promote bone formation and thus orderly regulate the inflammation and osteogenic microenvironment in the bone defect area. Furthermore, this barrier membrane is simple to prepare, uses widely available and cost-effective raw materials, and can effectively meet the needs of bone defect repair. Attached Figure Description
[0018] Figure 1 In Embodiment 1 of this invention, GelMA, GelMA-DOP, and Gel... 1 H NMR spectrum.
[0019] Figure 2 The viscosity of the GelMA-DOP and PAA double crosslinked network is given when the mass ratio of GelMA to DOPAC is 1:1 and 2:1 in Example 3 of this invention.
[0020] Figure 3 This describes the printing performance of the dual cross-linked network hydrogel ink in Example 3 of the present invention when the volume ratio of GelMA-DOP solution to PAA is 1:1.
[0021] Figure 4 This describes the printing performance of the dual cross-linked network hydrogel ink in Example 3 of the present invention when the volume ratio of GelMA-DOP solution to PAA is 1:2.
[0022] Figure 5 This describes the printing performance of the dual cross-linked network hydrogel ink in Example 3 of the present invention when the volume ratio of GelMA-DOP solution to PAA is 1:3.
[0023] Figure 6 The spherical morphology of the pore-forming agent when the mass ratio of OSA to 5-ASA is 1:0 in Example 4 of the present invention.
[0024] Figure 7This describes the spherical morphology of the pore-forming agent when the mass ratio of OSA to 5-ASA is 1:1 in Example 4 of the present invention.
[0025] Figure 8 This is a photograph showing the overall appearance of the barrier membrane in Embodiment 5 of the present invention.
[0026] Figure 9 ALP staining was performed on rBMSC cells treated with barrier membrane extract for 14 days in Example 6 of this invention.
[0027] Figure 10 The images show the establishment of a rat skull critical bone defect model and the implantation of a barrier membrane in Example 7 of this invention (A) and a Micro-CT three-dimensional reconstruction image after 8 weeks (B). Detailed Implementation
[0028] To provide a clearer understanding of the technical features, objectives, and beneficial effects of this invention, the technical solution of this invention is described in detail below, but this should not be construed as limiting the scope of implementation of this invention. In this invention, materials, reagents, or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0029] The specific implementation of the present invention will be described in detail below with reference to specific embodiments.
[0030] Example 1: Preparation of methacrylamide gelatin (GelMA) and catechol-modified GelMA (GelMA-DOP), the specific steps are as follows:
[0031] Preparation of GelMA freeze-dried sponge: 10g of gelatin (Gel) with a strength of 250g Bloom was dissolved in 100mL of deionized water (ddH2O). After stirring and dissolving, 8mL of methacrylic anhydride was added dropwise at a rate of 0.25mL / min. The reaction was carried out at room temperature in the dark for 2h. After the reaction was completed, the solution was placed in a dialysis bag with a molecular weight cutoff of 3500KDa and dialyzed in the dark for 72h. After freeze-drying, GelMA freeze-dried sponge was obtained.
[0032] Preparation of GelMA-DOP lyophilized sponge: 4g of the prepared GelMA lyophilized sponge was dissolved in 100mL ddH2O. 2g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and 1.2g of N-hydroxysuccinimide (NHS) were added to activate the amino groups on the GelMA molecular chain. Subsequently, 4g of 3,4-dihydroxyphenylacetic acid (DOPAC) was added, and the reaction was carried out overnight at 37℃ in the dark. After the reaction was completed, the solution was placed in a dialysis bag with a molecular weight cutoff of 3500 kDa and dialyzed in the dark for 72 hours. After freeze-drying, GelMA-DOP lyophilized sponge was obtained.
[0033] Depend onFigure 1 shown 1 The HNMR spectrum shows that the double peak at chemical shifts of 5.0-6.0 proves that -C=C- has been successfully grafted onto Gel, indicating the successful synthesis of GelMA; the peak at chemical shifts of 6.5-7.0 proves that the benzene ring has been successfully grafted onto GelMA, indicating the successful synthesis of GelMA-DOP.
[0034] Example 2: Preparation of adhesive double cross-linked network hydrogel ink, the specific steps are as follows:
[0035] 200 mg of the GelMA-DOP lyophilized sponge prepared in Example 1 was dissolved in 0.8 mL of ddH2O to obtain a GelMA-DOP solution. 2 mL of polyacrylic acid solution (PAA) with a molecular weight of 5000 kDa was added and stirred evenly. Then, 10 mg of lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP) was added. Under ultraviolet light irradiation at a wavelength of 365 nm, an adhesive double cross-linked network hydrogel ink was formed.
[0036] Example 3: Screening of key process parameters for 3D printing of adhesive layers. The specific steps are as follows:
[0037] Screening of the mass ratio of GelMA freeze-dried sponge to DOPAC: GelMA-DOP freeze-dried sponge was prepared according to the steps in Example 1. The mass ratio of GelMA freeze-dried sponge to DOPAC was set to 1:1 and 2:1, respectively, and then mixed with PAA to form a double crosslinked network. The network viscosity was tested using a rheometer. Figure 2 The results showed that both ratios of the dual cross-linked network exhibited shear thinning characteristics (viscosity decreased with increasing shear rate, which meets the requirements of 3D printing inks). Furthermore, the viscosity was higher when the mass ratio of GelMA freeze-dried sponge to DOPAC was 1:1, which is more conducive to printing. Therefore, the preferred mass ratio of GelMA freeze-dried sponge to DOPAC is 1:1.
[0038] Screening of GelMA-DOP solution to PAA volume ratio: Based on the above-preferred GelMA to DOPAC mass ratio (1:1), a GelMA-DOP solution was prepared, and its volume ratio to PAA was set to 1:1, 1:2, and 1:3, respectively. The 3D printing extrusion performance of inks with each ratio was tested. When the volume ratio of GelMA-DOP solution to PAA was 1:1, the double crosslinked network hydrogel ink curled during extrusion. Figure 3 ), further 3D printing is not possible; when the volume ratio of GelMA-DOP solution to PAA is 1:2, the double cross-linked network hydrogel ink can be successfully extruded through the 3D printer. Figure 4It possesses excellent printing performance; when the volume ratio of GelMA-DOP solution to PAA is 1:3, the double cross-linked network hydrogel ink forms droplets upon extrusion. Figure 5 If the solution is not fully 3D printed, further 3D printing is not possible. Therefore, a volume ratio of GelMA-DOP solution to PAA of 1:2 is preferred.
[0039] Example 4: Preparation of calcium ion-crosslinked oxidized sodium alginate (OSA) composite 5-aminosalicylic acid (5-ASA) microspheres, the specific steps are as follows:
[0040] Preparation of OSA freeze-dried sponge: 10g of sodium alginate with a viscosity ≥2000 (cP) was dissolved in 100mL ddH2O. After stirring and dissolving, 0.22g of sodium periodate was added, and the reaction was carried out overnight at 4℃. After the reaction was completed, 500μL of ethylene glycol was added to quench the reaction. The solution was then placed in a dialysis bag with a molecular weight cutoff of 3500KDa and dialyzed in the dark for 72h. After freeze-drying, OSA freeze-dried sponge was obtained.
[0041] Preparation and ratio screening of calcium ion-crosslinked OSA composite 5-ASA microspheres:
[0042] Dissolve 100 mg of OSA lyophilized sponge in 10 mL of ddH2O, and add 0 mL of 5-ASA aqueous solution. Drop this solution into a calcium chloride solution using a microfluidic chip to obtain calcium ion-crosslinked OSA microspheres. Figure 6 The results show that when the mass ratio of OSA to 5-ASA is 1:0, the OSA molecular chains break and the molecular weight decreases, making it impossible to form a regular spherical pore-forming agent morphology.
[0043] 200 mg of OSA lyophilized sponge was dissolved in 10 mL of ddH2O to obtain an OSA aqueous solution. 200 mg of 5-ASA was also dissolved in 10 mL of ddH2O to obtain a 5-ASA aqueous solution. Equal volumes of the OSA and 5-ASA aqueous solutions were mixed and reacted at room temperature for 72 h to obtain an OSA-5-ASA composite solution. This solution was then dropwise into a calcium chloride solution (obtained by dissolving 5 g of calcium chloride in 100 mL of ddH2O) using a microfluidic chip to obtain uniformly sized calcium-crosslinked OSA-5-ASA composite microspheres. Figure 7 The results show that when the mass ratio of OSA to 5-ASA is 1:1, the presence of the benzene ring in 5-ASA enhances the interaction between chains, thereby stabilizing the spherical morphology of the pore-forming agent. Therefore, a mass ratio of OSA to 5-ASA of 1:1 is preferred.
[0044] Example 5: Preparation of a self-fixing barrier membrane with gradient porosity;
[0045] This embodiment aims to construct a self-fixing barrier membrane consisting of three layers from soft tissue to bone tissue: a barrier layer, a drug-loaded pore-forming layer, and an adhesion layer. These three layers form a gradient pore structure through differences in pore size. The specific steps are as follows:
[0046] 10g of the GelMA lyophilized sponge prepared in Example 1 was dissolved in 100mL of ddH2O to prepare a 10% GelMA solution. 500mg of LAP was added, and a dense barrier layer was formed under 365nm UV irradiation. 1mg of the calcium ion-crosslinked OSA composite 5-ASA microspheres prepared in Example 4 was incorporated into 1mL of the prepared GelMA solution (microspheres act as pore-forming agents). 5mg of LAP was added, and a drug-loaded pore-forming layer with micron-level pores was formed under 365nm UV irradiation (the microspheres subsequently degrade to form pores, allowing osteoblasts to grow in, while simultaneously releasing 5-ASA and Ca2+). 2+ The layer is then tightly bonded to the barrier layer. Following the steps of Example 2, a double cross-linked network hydrogel ink is prepared and printed onto the other side of the drug-loaded pore-forming layer using a 3D printer, forming an adhesion layer with millimeter-scale pores (achieving self-fixation to bone tissue through hydrogen bonding between GelMA-DOP and PAA).
[0047] Figure 8 The results showed that the barrier membrane has an asymmetric Janus structure, with one side smooth and the other porous, and its thickness meets the basic requirements, so it will not cause excessive tissue tension during suturing; scanning electron micrographs further confirmed the above conclusions.
[0048] Example 6: In vitro verification of the osteogenic properties of the barrier membrane, the specific steps are as follows:
[0049] The barrier membrane prepared in Example 5 was immersed in 5 mL of rBMSCs culture medium and incubated overnight at 37°C to prepare a barrier membrane extract. The effect of the barrier membrane extract treatment on rat bone marrow mesenchymal cells (rBMSCs) was determined by alkaline phosphatase (ALP) staining. Three experimental groups were set up: a blank control group (rBMSCs culture medium only), an inflammation-induced group (rBMSCs + lipopolysaccharide (LPS), simulating the inflammatory environment of bone defects), and a barrier membrane group (rBMSCs + barrier membrane extract). After 14 days of cell treatment, ALP staining was performed, and the results showed (…). Figure 9 Compared with the control group and the inflammation-induced group (LPS), the barrier membrane group showed a significantly increased number of ALP-positive cells and deeper staining. This indicates that the barrier membrane can effectively promote osteogenic differentiation of rBMSCs compared with the control group and the inflammation-induced group.
[0050] Example 7: In vivo animal validation of the effect of the barrier membrane on bone regeneration, the specific steps are as follows:
[0051] The barrier membrane prepared in Example 5 was implanted into the critical skull bone defect in rats. Figure 10 (See section A). Three experimental groups were set up: blank control / Bio-Gide group: no barrier membrane was implanted at the bone defect site, or a Bio-Gide membrane was implanted; blank control / barrier membrane group: no barrier membrane was implanted at the bone defect site, or a barrier membrane prepared in this invention was implanted; Bio-Gide / barrier membrane group: a Bio-Gide membrane was implanted at the bone defect site, or a barrier membrane prepared in this invention was implanted. After 8 weeks, Micro-CT three-dimensional reconstruction images showed that, compared with the blank control group and the Bio-Gide group, the bone regeneration volume of the barrier membrane group of this invention was significantly increased ( Figure 10 (B) This study demonstrates that the barrier membrane has the best effect on promoting bone tissue regeneration in vivo.
[0052] The above are merely preferred embodiments of the present invention. It should be noted that those skilled in the art can make several modifications and improvements without departing from the concept of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the implementation of the present invention or the practicality of the patent.
Claims
1. A method for preparing a self-fixing barrier membrane with gradient porosity, characterized in that, The self-fixing barrier membrane comprises, sequentially from soft tissue to bone tissue, a barrier layer, a drug-loaded pore-forming layer, and an adhesion layer, with a gradient pore structure formed between the three layers through differences in pore size; the preparation method includes the following steps: Preparation of the barrier layer: Gelatin with a strength of 250g Bloom was dissolved in ddH2O. After stirring and dissolving, methacrylic anhydride was added dropwise at a rate of 0.25ml / min and reacted at room temperature in the dark for 2h. After the reaction was completed, the solution was placed in a dialysis bag and dialyzed in the dark for 72h. After freeze-drying, GelMA lyophilized sponge was obtained. The GelMA lyophilized sponge was dissolved in ddH2O to obtain GelMA solution. The photoinitiator lithium phenyl (2,4,6-trimethylbenzoyl) phosphate was added, and a barrier layer was formed under ultraviolet light irradiation at a wavelength of 365nm. Preparation of drug-loaded pore-forming layer: Sodium alginate was dissolved in ddH2O, stirred until dissolved, and sodium periodate was added. The reaction was carried out overnight at 4℃. After the reaction was completed, 500 μL of ethylene glycol was added to quench the reaction. The solution was placed in a dialysis bag and dialyzed in the dark for 72 h. After freeze-drying, OSA lyophilized sponge was obtained. OSA lyophilized sponge was dissolved in ddH2O to obtain OSA aqueous solution. 5-aminosalicylic acid aqueous solution prepared by dissolving 5-aminosalicylic acid in ddH2O was added. The reaction was carried out at room temperature for 72 h to obtain OSA composite 5-ASA solution. The solution was dripped into calcium chloride solution through a microfluidic chip to obtain uniformly sized calcium ion crosslinked OSA composite 5-ASA microspheres. The calcium ion crosslinked OSA composite 5-ASA microspheres were incorporated into GelMA solution, and phenyl (2,4,6-trimethylbenzoyl) lithium phosphate was added. The drug-loaded pore-forming layer was formed under ultraviolet light irradiation at a wavelength of 365 nm. Preparation of the adhesive layer: GelMA lyophilized sponge was dissolved in ddH2O, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide were added to activate the amino groups on the GelMA molecular chain. Then, 3,4-dihydroxyphenylacetic acid was added, and the reaction was carried out overnight at 37°C in the dark. After the reaction was completed, the solution was placed in a dialysis bag and dialyzed in the dark for 72 hours. After freeze-drying, GelMA-DOP lyophilized sponge was obtained. GelMA-DOP lyophilized sponge was dissolved in ddH2O to obtain GelMA-DOP solution. Polyacrylic acid solution was added, and after stirring evenly, lithium phenyl (2,4,6-trimethylbenzoyl) phosphate was added. Under ultraviolet light irradiation at a wavelength of 365 nm, an adhesive double cross-linked network hydrogel ink was formed. The ink was printed on the side of the drug-loaded pore-forming layer away from the barrier layer using a 3D printer to form an adhesive layer with millimeter-scale 3D printed pores.
2. The preparation method according to claim 1, characterized in that, When preparing the barrier layer, the ratio of gelatin to methacrylic anhydride is 1000:0-1000 (g / mL); the ratio of GelMA lyophilized sponge to ddH2O is 0-20:100 (g / mL).
3. The preparation method according to claim 2, characterized in that, The ratio of gelatin to methacrylic anhydride is 1000:800 (g / mL); the ratio of GelMA freeze-dried sponge to ddH2O is 1:10 (g / mL).
4. The preparation method according to claim 1, characterized in that, When preparing the drug-loaded pore-forming layer, the ratio of sodium alginate to ddH2O is 1-1000:100 (g / mL); the mass ratio of OSA lyophilized sponge to 5-aminosalicylic acid is 1-40:1; the ratio of calcium chloride to ddH2O in the calcium chloride solution is 1-50:100 (g / mL); and the pore size of the calcium ion crosslinked OSA composite 5-ASA microspheres is 100-300 μm.
5. The preparation method according to claim 4, characterized in that, The ratio of sodium alginate to ddH2O is 1:100 (g / mL); the mass ratio of OSA freeze-dried sponge to 5-aminosalicylic acid is 1:1; the ratio of calcium chloride to ddH2O in the calcium chloride solution is 5:100 (g / mL); and the pore size of the calcium ion crosslinked OSA composite 5-ASA microspheres is 188 μm.
6. The preparation method according to claim 1, characterized in that, When preparing the adhesive layer, the mass ratio of GelMA freeze-dried sponge to 3,4-dihydroxyphenylacetic acid is 1:0-10; the ratio of GelMA-DOP freeze-dried sponge to ddH2O is 1-50:100 (g / mL); the volume ratio of GelMA-DOP solution to polyacrylic acid solution is 1:0-10; and the 3D printing pore size is 1-4 cm.
7. The preparation method according to claim 6, characterized in that, The mass ratio of GelMA freeze-dried sponge to 3,4-dihydroxyphenylacetic acid is 1:1; the ratio of GelMA-DOP freeze-dried sponge to ddH2O is 20:80 (g / mL); the volume ratio of GelMA-DOP solution to polyacrylic acid solution is 1:2; and the 3D printing pore size is 2 cm.
8. A self-fixing barrier membrane with gradient porosity prepared by the preparation method according to any one of claims 1-7.
9. The use of the self-fixing barrier membrane according to claim 8 in the preparation of a barrier material for guided bone regeneration.
10. The application of the self-fixing barrier membrane according to claim 8 in the preparation of biomaterials for bone tissue repair.
